2010
DOI: 10.1007/s00426-010-0313-4
|View full text |Cite
|
Sign up to set email alerts
|

No conflict control in the absence of awareness

Abstract: Altogether, the results support the conclusion that awareness of visual primes is important for controlling conflict in visuo-motor processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
63
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 50 publications
6
63
1
Order By: Relevance
“…Nevertheless, as task relevance of conflict is an important factor for conflict adaptation (Hazeltine, Lightman, Schwarb, & Schumacher, 2011), further research is needed that directly manipulates task relevance for perceptual conflict (for a relevant methodology, see Ansorge et al, 2011). Concerning the locus of conflict adaptation in terms of level of consciousness, we did not observe unconsciously triggered conflict adaptation on RTs either in Experiment 1 or 3.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Nevertheless, as task relevance of conflict is an important factor for conflict adaptation (Hazeltine, Lightman, Schwarb, & Schumacher, 2011), further research is needed that directly manipulates task relevance for perceptual conflict (for a relevant methodology, see Ansorge et al, 2011). Concerning the locus of conflict adaptation in terms of level of consciousness, we did not observe unconsciously triggered conflict adaptation on RTs either in Experiment 1 or 3.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, the observation of unconsciously triggered conflict adaptation has important implications concerning our definition of consciousness. Note, however, that other researchers have failed to observe unconsciously triggered conflict adaptation (e.g., Ansorge, Fuchs, Khalid, & Kunde, 2011;Frings & Wentura, 2008), suggesting that extant conclusions about the role of unconscious stimuli in inducing cognitive control have to be taken with caution.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In incompatible trials, it would detect response conflict and suppress the direct route, which is responsible for the activation of the incorrect response. The suppression of the direct route would lead, in turn, to a reduction of the Simon effect in the following trial (e.g., Ansorge, Fuchs, Khalid, & Kunde, 2011). In line with this view, sequential modulations of the Simon effect should occur only when we have to respond and want to avoid the selection of the incorrect response, whereas it should not be observed when no response has to be selected.…”
mentioning
confidence: 88%
“…Although it is now widely accepted that low-level processing, such as the processing of color and shape (Breitmeyer, Ro, & Singhal, 2004;Klotz & Neumann, 1999;Ro et al, 2009;Schmidt, 2002), occurs unconsciously, evidence for unconscious high-level information processing remains mixed. For example, whereas some studies have shown cognitive control (e.g., conflict adaptation, error detection) without perceptual awareness (O'Connell et al, 2007;van Gaal, Lamme, & Ridderinkhof, 2010), other studies suggest that awareness is necessary for these high-level processes (Ansorge, Fuchs, Khalid, & Kunde, 2011;Kunde, 2003;Woodman, 2010). A possible reason for these discrepancies may be due to restricted visual inputs that are frequently used to study visual awareness rather than the necessity of awareness for higher level processing per se.…”
mentioning
confidence: 99%